1996
DOI: 10.1002/(sici)1099-114x(199605)20:5<385::aid-er157>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of multicomponent liquid fuel droplets

Abstract: SUMMARYA theoretical investigation on evaporation of a two-component liquid fuel droplet in high-temperature quiescent gaseous surroundings has been made from the numerical solution of conservation equations of heat, mass and momentum transports in the carrier and droplet phases. Liquid fuel droplets containing (i) components of widely varying volatilities, namely, n-hexane and n-hexadecane and (ii) components of closely spaced volatilities, namely, n-hexane and benzene, have been considered for the studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Negeed et al reported that the maximum diameter droplet spread increases with the increase of Weber number, size, or impinging velocity of the droplet. Bhattacharya et al compared the inter‐diffusion model and rapid mixing model in predicting the droplets vaporization of two‐component fuel. They reported that the inter‐diffusion model is more successful in predicting the experimental data, as it assumes that more volatile component of the fuel firstly vaporizes out of the droplet surface while the internal composition remains same.…”
Section: Oxy‐fuel Combustion In Conventional Combustion Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negeed et al reported that the maximum diameter droplet spread increases with the increase of Weber number, size, or impinging velocity of the droplet. Bhattacharya et al compared the inter‐diffusion model and rapid mixing model in predicting the droplets vaporization of two‐component fuel. They reported that the inter‐diffusion model is more successful in predicting the experimental data, as it assumes that more volatile component of the fuel firstly vaporizes out of the droplet surface while the internal composition remains same.…”
Section: Oxy‐fuel Combustion In Conventional Combustion Systemsmentioning
confidence: 99%
“…Negeed et al [107] reported that the maximum diameter droplet spread increases with the increase of Weber number, size, or impinging velocity of the droplet. Bhattacharya et al [108] compared the inter-diffusion model and rapid mixing model in predicting the droplets vaporization of two- consequently increased the reaction kinetics and significantly reduced the formation of NO x and CO. They reported an increase of 1.9 orders of magnitude in the radiation from the flame in the swirl air combustor compared with that in the experimentally tested one.…”
Section: General Combustion Characteristics Of Liquid Fuelsmentioning
confidence: 99%
“…The spray outer zone was found to ex hibit larger diameter than those in the inner zone which can be attributed to the effect of spray-induced ambient air flow. Bhattacharya et al [8] used numerical model to investigate the evaporation of two component fuel droplets. Similar trend has also been observed by Ghassemi et al [6] in his experiment on evaporation of kerosene droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11 reveals that for the major portion of the droplet life, the droplet temperature remains nearly uniform. Hence, the use of in"nite conductivity model for the energy equation, as done by Bhattacharya et al (1996) seems justi"ed. Towards the middle of the droplet life, temperature of the entire droplet sharply increases without noticeable change in droplet size.…”
Section: Characterisitics Of Multicomponent Droplet Combustionmentioning
confidence: 99%